AUTOMATED ASSESSMENT TECHNOLOGY BASED ON ARTIFICIAL INTELLIGENCE - Norboyev S. (Modern American Journals, 2026)
This article analyzes the importance of automated assessment technologies based on artificial intelligence in education and professional activities. It is justified that the development of digital technologies creates the need to automate assessment processes. It is shown that the subjectivity and human factor in traditional assessment methods can be reduced using artificial intelligence. The article covers the content of the concepts of artificial intelligence and automated assessment. The role of machine learning, natural language processing and speech recognition technologies in assessment is analyzed. The application of artificial intelligence-based assessment systems in education, personnel selection and IT is considered. The advantages of these technologies such as speed and objectivity are revealed. At the same time, the problems of algorithmic bias and data security are noted.
Keywords: Artificial intelligence, automated assessment, machine learning, natural language processing, digital education, assessment systems, education quality.